Successful engraftment of donor marrow following allogeneic hematopoietic cell transplantation in autosomal recessive Hyper IgE syndrome due to DOCK8 deficiency - McDonald, Douglas R. (2010)
A child with homozygous partial deletion of the DOCK8 gene showed characteristic clinical findings of autosomal recessive hyper-IgE syndrome and full donor chimerism early after matched sibling bone marrow transplantation.